2008
DOI: 10.1111/j.1365-2818.2008.02027.x
|View full text |Cite
|
Sign up to set email alerts
|

Total internal reflection microscopy for live imaging of cellular uptake of sub‐micron non‐fluorescent particles

Abstract: Key words. Drug delivery, endocytosis, evanescent wave microscopy, imaging systems, live-cell imaging, medical and biological imaging, microscopy, total internal reflection fluorescence. SummaryThis paper presents a simple, high-resolution, non-fluorescent imaging technique called total internal reflection microscopy (TIRM) and demonstrates its potential application to realtime imaging of live cellular events. In addition, a novel instrument is introduced that combines the simplicity of TIRM with the specifici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 25 publications
(24 reference statements)
0
26
0
Order By: Relevance
“…Other applications were to elucidate the role of ceramide in membrane restructuring (Ira et al 2009), the organization of bacterial light harvesting complex 2 (Dewa et al 2006), the role of cholesterol in antibody binding ), EGFR activation by EGF (Sako et al 2000;Cannon et al 2005;Teramura et al 2006), and the phase preference of peptides (Choucair et al 2007). Membrane curvature, exocytosis, and endocytosis are some other topics in which TIRF is successfully applied (Merrifield et al 2002(Merrifield et al , 2005Byrne et al 2008;Nagamatsu and Ohara-Imaizumi 2008;Joselevitch and Zenisek 2009;Ohara-Imaizume et al 2009;Aoki et al 2010;Gorg et al 2010;Lam et al 2010).…”
Section: Tirf Applications On Membrane Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other applications were to elucidate the role of ceramide in membrane restructuring (Ira et al 2009), the organization of bacterial light harvesting complex 2 (Dewa et al 2006), the role of cholesterol in antibody binding ), EGFR activation by EGF (Sako et al 2000;Cannon et al 2005;Teramura et al 2006), and the phase preference of peptides (Choucair et al 2007). Membrane curvature, exocytosis, and endocytosis are some other topics in which TIRF is successfully applied (Merrifield et al 2002(Merrifield et al , 2005Byrne et al 2008;Nagamatsu and Ohara-Imaizumi 2008;Joselevitch and Zenisek 2009;Ohara-Imaizume et al 2009;Aoki et al 2010;Gorg et al 2010;Lam et al 2010).…”
Section: Tirf Applications On Membrane Dynamicsmentioning
confidence: 99%
“…Recently, it has been shown that TIRF has the capacity to show the adsorption of proteins and peptides to lipids in SLBs (Fox et al 2009;Jorgensen et al 2009). TIRF was combined with singleparticle tracking to show the enrichment of GPI-anchored proteins in sphingolipid rich regions, as proposed by lipid raft theory Membrane curvature, exocytosis, and endocytosis are some other topics in which TIRF is successfully applied (Merrifield et al 2002(Merrifield et al , 2005Byrne et al 2008;Nagamatsu and Ohara-Imaizumi 2008;Joselevitch and Zenisek 2009; Ohara-Imaizume et al 2009;Aoki et al 2010;Gorg et al 2010;Lam et al 2010). …”
mentioning
confidence: 99%
“…25 The penetration depth (decay) of the evanescent field varies with incident angle, ranging from approximately 180 nm when the incident beam is 2 degrees above the critical angle to about 120 nm when the incident beam angle is increased by a further 5 degrees. Similar was previously reported for variable TIRF microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…The specificity of labeling is also at the same time the main advantage and the main limitation of fluorescence imaging because it prevents whole sample visualization. In label-free evanescent microscopy (EM), configurations similar to TIRF (prism-based or through-the-objective) have been proposed [7,8]. However, in the latter case, these evanescent techniques have not spread much, with a relative preference for the prism-based configuration also called total internal reflection microscopy (TIRM) [9,10].…”
Section: Biophotonicsmentioning
confidence: 99%